FEATURES OF CRYSTALLIZATION FOR METALLIC BATH DURING ELECRTOSLAG BUILDING-UP IN CURRENT-CARRYING CRYSTALLIZER - Netyaga, Anton; Kuskov, Yuri (Scientific Journal "Metallurgy", 2022)
There is noted possibility of fine-grained built-up metal receipt during electro-slag building-up in current-carrying crystallizer. The analysis of influence of the electromagnetic action on crystallization of liquid metal in congenial technologies of welding, building-up and meltback, and also continuous pouring of steel is executed. There is set vacuity of only mind about the mechanism of crystallization of metal in such conditions. On the base of substantial hypotheses study the mechanism of increase for metal discreteness, built-up in currentcarrying crystallizer such, which united both the thermophysical component of crystallization and magnetic substance as an independent element of action is offered.